Extracellular vesicles from monocyte/platelet aggregates modulate human atherosclerotic plaque reactivity - Silvia Oggero; Monica deGaetano; Simone Marcone; Stephen Fitzsimons; Andreia L. Pinto; Dinara Ikramova; Mary Barry; David Burke; Trinidad Montero‐Melendez; Dianne Cooper; Thomas Burgoyne; Orina Belton; et al. (Journal of Extracellular Vesicles, 2021)
Abstract Extracellular vesicles (EVs) are emerging as key players in different stages of atherosclerosis. Here we provide evidence that EVs released by mixed aggregates of monocytes and platelets in response to TNF‐α display pro‐inflammatory actions on endothelial cells and atherosclerotic plaques. Tempering platelet activation with Iloprost, Aspirin or a P2Y12 inhibitor impacted quantity and phenotype of EV produced. Proteomics of EVs from cells activated with TNF‐α alone or in the presence of Iloprost revealed a distinct composition, with interesting hits like annexin‐A1 and gelsolin. When added to human atherosclerotic plaque explants, EVs from TNF‐α stimulated monocytes augmented release of cytokines. In contrast, EVs generated by TNF‐α together with Iloprost produced minimal plaque activation. Notably, patients with coronary artery disease that required percutaneous coronary intervention had elevated plasma numbers of monocyte, platelet as well as double positive EV subsets. In conclusion, EVs released following monocyte/platelet activation may play a potential role in the development and progression of atherosclerosis. Whereas attenuating platelet activation modifies EV composition released from monocyte/platelet aggregates, curbing their pro‐inflammatory actions may offer therapeutic avenues for the treatment of atherosclerosis.